Sentence Errors in Descriptive Text: A Study on How Students Understand English Sentence Patterns - Juliansyah Juliansyah; Yessy Harun (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
This research is addressed to discover the mistakes carried out by the students in writing simple sentences and complex sentences of descriptive text in the form of description paragraph. The research participants are undergraduate students of the first semester. The research objective is identifying kinds of sentence errors in simple sentences and complex sentences conducted by the students in writing a descriptive paragraph. The research data were obtained from the results of the questionnaires. The data tells that, firstly,  96% of total students did not come from a language major when they were in high school y are  and tests given; secondly, 63% of students learn English in one week more than once (generally 2x80 minutes), and thirdly, only 29% of students admit to having studied very ‘complex’ sentences.  Furthermore, the study identifies three types of students’ mistakes related to writing simple sentences. Those mistakes are: 1) mistakes in using the verb form from the review of the English structure and of conformity to the subject of the sentence, 2) the use of types of words in the subject and or subject complement, and 3) the incompleteness of elements in simple sentences (no subject, or verbs, and or subject complement). In relation to the ability of writing complex sentences, there were four types of common mistakes related to complex sentences. They are: 1) mistakes in placing complementary clauses according to the type of clause, 2) incomplete sentence elements, both in the main clause and in complementary clauses, 3) mistakes in using types of words in certain parts, both in the main and complementary clauses, and 4) mistakes in using conjunctions. Based on the research results, the researcher concludes that the ability to write complex sentences should be of greater concern both students and lecturers for better writing ability.